2011
DOI: 10.1007/s13365-011-0038-1
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon signaling limits reoviral tropism within the brain and prevents lethal systemic infection

Abstract: In vivo and ex vivo models of reoviral encephalitis were utilized to delineate the contribution of type I interferon (IFN) to the host’s defense against local central nervous system (CNS) viral infection and systemic viral spread. Following intracranial (i.c.) inoculation with either serotype 3 (T3) or serotype 1 (T1) reovirus, increased expression of IFN-α, IFN-β, and myxovirus-resistance protein (Mx1; a prototypical IFN stimulated gene) was observed in mouse brain tissue. Type I IFN receptor deficient mice (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 41 publications
4
32
0
Order By: Relevance
“…Collectively, maturation of neurons is associated with increased levels of IFN signaling pathway components (33,34). Mature neurons are able to produce an innate immune response upon virus infection (28,(30)(31)(32)(33). Increased basal levels of Irf-3 and Irf-7 expression could contribute to an enhanced host response to infection.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, maturation of neurons is associated with increased levels of IFN signaling pathway components (33,34). Mature neurons are able to produce an innate immune response upon virus infection (28,(30)(31)(32)(33). Increased basal levels of Irf-3 and Irf-7 expression could contribute to an enhanced host response to infection.…”
Section: Figmentioning
confidence: 99%
“…These studies suggest a potential role for IFN signaling in maturation-dependent neuronal restriction of neuronotropic virus replication. Neurons can induce IFN signaling upon infection (28,(30)(31)(32)(33), and IFN expression is increased during maturation of cultured neurons (34). However, autocrine IFN signaling has not been implicated in maturation-dependent control of virus replication (33).…”
mentioning
confidence: 99%
“…Upregulation of Daxx was previously reported in bone marrow cells following type I IFN exposure (46,47). We previously showed that interferon signaling is initiated in the reovirus-infected brain and serves to limit local viral tropism and systemic viral spread (11,40,44). Thus, we hypothesized that IFN was driving Daxx upregulation during reovirus infection.…”
Section: Brain Expression Of Daxx Mrna and Protein Is Upregulated Durmentioning
confidence: 80%
“…2). However, Daxx was not upregulated in reovirus-infected brain slices prepared from IFNAR Ϫ/Ϫ donor mice, despite the fact that viral growth is enhanced in this context (40). This indicated that the type I interferon arm of innate immunity is the major mechanism underlying reovirus-induced Daxx upregulation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation